The Effect of Motivation and Working Environment on Teachers’ Performance with Job Satisfaction as Intervening Variable: The Case of PPPK Junior High School at Penukal Abab Lematang Regency - Sari, Ayu Vramita; Idris, Muhammad; Yamaly, Fadhil (Training & Research Institute - Jeramba Ilmu Sukses, 2025)
This study aims to determine the influence of work motivation and work environment on teacher performance, with job satisfaction as an intervening variable at the PK teachers SMP Negeri of Penukal Abab Lematang Ilir Regency. This type of research is quantitative. The variables used in this study are work motivation, work environment, job satisfaction, and performance. The sample in this study consists of 120 PPPK teachers at SMP Negeri in Penukal Abab Lematang Ilir Regency, selected using proportional random sampling. The primary data used in this study was collected through a questionnaire. The data analysis technique used is Structural Equation Modeling (SEM) with the LISREL software application. The results of this study show that (1) work motivation has a positive and significant effect on job satisfaction, (2) work environment has a positive and significant effect on job satisfaction, (3) work motivation has a positive and significant effect on performance, (4) work environment has a positive and significant effect on performance, (5) job satisfaction does not have a significant effect on performance at the PPPK teachers SMP Negeri of Penukal Abab Lematang Ilir Regency.